2023
DOI: 10.3390/ijms24076060
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Caryophyllene Modifies Intracellular Lipid Composition in a Cell Model of Hepatic Steatosis by Acting through CB2 and PPAR Receptors

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease; however, no specific pharmacological therapy has yet been approved for this condition. Plant-derived extracts can be an important source for the development of new drugs. The aim of this study was to investigate the effects of (E)-β-caryophyllene (BCP), a phytocannabinoid recently found to be beneficial against metabolic diseases, on HepG2 steatotic hepatocytes. Using a fluorescence-based lipid quantification assay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Additionally, it can decrease liver fibrosis by activating hepatic peroxisomes or inhibiting stellate cell activation [110,111]. In a recent study, a newly discovered phytocannabinoid (E)-β-caryophyllene was found to counteract the reduction of PPARα in hepatic steatosis [112].…”
Section: Peroxisome Proliferator-activated Receptormentioning
confidence: 99%
“…Additionally, it can decrease liver fibrosis by activating hepatic peroxisomes or inhibiting stellate cell activation [110,111]. In a recent study, a newly discovered phytocannabinoid (E)-β-caryophyllene was found to counteract the reduction of PPARα in hepatic steatosis [112].…”
Section: Peroxisome Proliferator-activated Receptormentioning
confidence: 99%
“…Saikosaponin D and diosgenin serve as PPARα agonists, promoting PPARα-mediated fatty acid oxidation and inhibiting CD36-mediated fatty acid uptake and SREBP-1c-mediated de novo lipogenesis ( 128 , 129 ). Oleanolic acid, a pentacyclic triterpenoid, and (E)-β-caryophyllene, a bicyclic sesquiterpene hydrocarbon, act as dual activator of PPARα and PPARγ, decreasing hyperglycemia and lipid accumulation ( 130 , 131 ). Furthermore, Saikosaponin A and ginsenoside 20(R/S)-Rg3 act as natural PPARγ activators, ameliorating hyperlipidemia and atherosclerosis ( 72 , 132 ).…”
Section: Natural Compounds In Regulation Of Pparsmentioning
confidence: 99%